Propel in collaboration with Unitama Property - Daily Express, (KK) (Daily Express (KK), 2012)
KUALA LUMPUR: Projek Penyelenggaraan Lebuhraya Bhd (Propel) and Uniutama Property Sdn Bhd will collaborate to secure infrastructure maintenance works.